Puzzling large-scale polarization in the galaxy cluster Abell 523. Issue 4 (7th July 2022) - Vacca, Valentina; Govoni, Federica; Murgia, Matteo; Perley, Richard A; Feretti, Luigina; Giovannini, Gabriele; Carretti, Ettore; Gastaldello, Fabio; Cova, Filippo; Marchegiani, Paolo; Battistelli, Elia; Boschin, Walter; et al.
ABSTRACT: Large-scale magnetic fields reveal themselves through diffuse synchrotron sources observed in galaxy clusters such as radio halos. Total intensity filaments of these sources have been observed in polarization as well, but only in three radio halos out of about 100 currently known. In this paper we analyse new polarimetric Very Large Array data of the diffuse emission in the galaxy cluster Abell 523 in the frequency range 1–2 GHz. We find for the first time evidence of polarized emission on scales of ∼2.5 Mpc. The total intensity emission is observed only in the central part of the source, likely due to observational limitations. To look for total intensity emission beyond the central region, we combine these data with single-dish observations from the Sardinia Radio Telescope and we compare them with multifrequency total intensity observations obtained with different instruments, including the LOw Frequency ARray and the Murchison Widefield Array. By analysing the rotation measure properties of the system and utilizing numerical simulations, we infer that this polarized emission is associated with filaments of the radio halo located in the outskirts of the system, in the peripheral region closest to the observer.